Antibiotic Sensitivity Pattern of Pathogens Isolated from Pus Culture- A Tertiary Care Hospital Based Study - Singh, Ankita; Verma, Vikash; Singh, Ritesh (Journal of Nepalgunj Medical College, 2019)
Background: Microbial pathogens cause human skin and soft tissue infections (SSTI) and surgical site infections (SSI) after surgical procedures. These can result in the production of pus, yellowish fluid comprising of dead WBCs and cellular debris. The microorganisms responsible for pus production vary greatly in relation to their spectrum of prevalence in different hospital and also in their antibiotic sensitivity. Further, the antibiotic sensitivity also changes because of the emergence of resistant strains. It is therefore, important that the common bacterial pathogens causing infection in a particular hospital and their sensitivity should be known. This will help in the choice of prophylactic antibiotic and in initiating the empirical antibiotic prescription for the infected cases before the culture sensitivity report is made available which takes about 2-3 days.Objective: To identify the spectrum of aerobic bacteria which are responsible for SSTI and SSI and their antibiotic sensitivity pattern.Method: This cross sectional hospital based study was conducted in Nepalgunj Medical College and Teaching Hospital (NGMCTH), Kohalpur from January 2019 to November 2019. These pus swabs were obtained from the Department of Surgery and Department of Gynaecology & Obstretics. Samples were cultured in the Microbiology laboratory of NGMCTH, Kohalpur. Identification and characterization of isolates were performed on the basis of Gram staining and cultural characteristics. Antibiotic sensitivity test was performed in vitro by Bauer-Kirby method. Collected data were statistically analyzed using SPSS 20.0 and Microsoft Excel 2015.Results: During the study period, a total number of 311 pus swabs were obtained among which only 164 (52.73%) pus swab showed bacterial growth. Out of 164 pus swabs, 150 pus swabs yielded monomicrobial growth (150 bacterial isolates) and 14 pus swabs yielded polymicrobial growth (33 bacterial isolates). Gram Negative Bacteria (60.1%) was more prevalent than Gram Positive Bacteria (39.9%). Combined together, the most common isolate was S. aureus (36.1%) followed by E.coli (24.0%), Klebsiella (14.2%), Enterobacter (11.5%), Pseudomonas (9.8%), S. pyogenes (3.3%) and Proteus (1.1%). S. aureus was highly sensitive to Doxycycline (90.6%), Chloramphenicol (81.5%), Amikacin (79.5%) and Ceftraixone (72.7%). S. pyogenes showed 100% sensitivity to Cefexime, Amikacin, Chloramphenicol, Azithromycin and 80% sensitivity to Doxycycline. Similarly, most common gram negative isolate E.coli showed higher sensitivity to Chloramphenicol(71.4%) and Amikacin (66.7%) , Klebsiella showed higher sensitivity to Doxycycline(92.3%), Gentamicin(87.5%) and Amikacin (81.0%), Enterobacter showed higher sensitivity to Amikacin(90.9%) and Pseudomonas was highly sensitive to Chloramphenicol (71.4%) and Amikacin (66.7%). Piperacillin, Amikacin, Gentamicin, Ofloxacin and Ceftriaxone showed 100% sensitivity to Proteus spp. Amoxyclav, Cefepime and Cefexime (except in S. pyogenes) showed least sensitivity in both gram negative and gram positive bacterial isolates.Conclusion: In our study, the most common isolate wasS. aureus. Amikacin, as a single drug was found to be effective for empirical therapy of both gram negative and gram positive bacteria whereas Doxycycline and Amikacin was found effective in gram positive isolates. Amoxyclav and Cefepimewas commonly resistant in all bacterial isolates.